The Effect of Dictogloss Technique on The Students’ Listening Comprehension at Stmik Prabumulih - Hepnyi Samosir; Nur Aini H (Intensive Journal, 2020)
This study is concerned with the effect of the dictogloss technique on the students’ listening comprehension. It uses an experimental design. The population of the study was the third semester Information Systems study program students of STMIK Prabumulih.  The samples were taken by applying random sampling technique. Pretest and posttest were carried out with participant students from the two classes, experimental and control class. The independent samples t-test was carried out to compare  the means of the two independent groups. The finding reveals that the tcount value was greater than the ttable value at the 0.05 significance level with df 62 (3.58>1.67). With the result of this calculation, the null hypothesis is successfully rejected. It means that the listening comprehension of the third semester students of STMIK Prabumulih taught by using dictogloss technique is higher than students taught with conventional technique and thus dictogloss technique significantly affect students’ listening comprehension.